A survey on awareness and knowledge among dentist practicing regenerative endodontics towards current regenerative endodontic protocols and the scaffolds used in regenerative dentistry - Saraswathi V. Naik; Aarathi J. Prakash; R. Prabhakar Attiguppe (Elsevier, 2023)
There are many inconsistencies in the protocols followed for Regenerative Endodontic Procedures (REP's).This study was formulated with an aim to conduct a survey among Pediatric Dentists, Endodontists and General Practioners treating Necrotic young permanent teeth to examine their awareness and Knowledge on Current Regenerative Endodontic Protocols and Scaffolds used in regenerative dentistry. Methods: A Cross-Sectional Survey was carried out amongst 100 Pediatric dentists,100 Endodontists and 100 General Practioners. It was web-based survey and the questionnaire was formulated and all the items in the questionnaire were tested for reliability and validity before circulation of the questionnaire for the purpose of the study. Results: The results of the study indicated that all the three groups were unaware that failure of cases should be reported to AEE (American Academy of Endodontics) REP Database and only 20.2, 20.1 and 0.3 % of Pediatric dentists,Endodontists and General Dentists preferred Regenerative Dentistry as a clinical protocol for REP. With respect to knowledge regarding irrigation and disinfection procedures all three groups were lacking in the knowledge regarding intracanal medicament for disinfection and the irrigation solutions. Conclusion: There is a lack of homogeneity in protocols followed for REP among those practicing Regenerative Endodontics as a protocol. Since it's an evolving science there is a need to bring about a uniformity in practices to increase the evidences to support the causal effect relation of regenerative endodontics.